2013
DOI: 10.3109/08880018.2013.852644
|View full text |Cite
|
Sign up to set email alerts
|

A Single Center Experience in 266 Patients of Infantile Malignancies

Abstract: The distribution of malignancy in infants is quite different from that which is found in older children. Although neuroblastoma is the most common infantile tumor in western countries, in our study leukemia is the most common infantile malignancy. Embryonal tumors such as neuroblastoma, Wilms tumor, retinoblastoma, and hepatoblastoma were more prevalent in infants. Solid tumors were the most common malignancy in infants which is followed by leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
5
4
0
Order By: Relevance
“…In the present study, infantile solid tumors constituted 7.3% (60 cases) of all pediatric solid tumors (835 cases) reported in the cytopathology division of our department during the study duration. The current study considered only the cytological diagnosis as compared to other studies which included cytological and histopathological diagnoses of infantile malignancies 2,7‐8 . Present study showed NB as the most common solid malignancy in infancy (25%) which is consistent with the literature 1,2,7‐8 …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the present study, infantile solid tumors constituted 7.3% (60 cases) of all pediatric solid tumors (835 cases) reported in the cytopathology division of our department during the study duration. The current study considered only the cytological diagnosis as compared to other studies which included cytological and histopathological diagnoses of infantile malignancies 2,7‐8 . Present study showed NB as the most common solid malignancy in infancy (25%) which is consistent with the literature 1,2,7‐8 …”
Section: Discussionsupporting
confidence: 88%
“…Earlier, Das et al from the pediatric oncology unit of our Institute had conducted a statistical study from 2003 to 2012. They reported 266 cases of infantile malignancies, of them, 193 cases were solid tumors 7 . In the present study, infantile solid tumors constituted 7.3% (60 cases) of all pediatric solid tumors (835 cases) reported in the cytopathology division of our department during the study duration.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…MDS is a clonal preleukemic disease state with cytopenia due to underproduction, abnormal differentiation, increased apoptosis, and varying degrees of leukemic blasts and carries a high risk of progression to leukemia. The incidence of both MDS and AML increases with age (7), but both can present in early childhood (8,9).…”
Section: Introductionmentioning
confidence: 99%